Accuracy of Pulmonary Nodule Volumetry at Different Exposure Parameters in Low-Dose Computed Tomography: A Phantom Study. Issue 6 (November 2019) - Liu, Jieke; Qing, Haomiao; Luo, Hongbing; He, Changjiu; Wang, Chunhua; Ren, Jing; Zhou, Peng
Abstract : Objective: To explore the exposure parameters with minimized radiation dose for accurate pulmonary nodule volumetry using low-dose computed tomography (LDCT). Methods: An anthropomorphic chest phantom with 11 pulmonary nodules (6 solid nodules and 5 ground-glass opacities) was scanned using 256-slice multidetector computed tomography scanner at various tube voltage and current (combinations of 80, 100 and 120 kV with 10 to 30 mAs). Raw data sets were reconstructed using the hybrid iterative reconstruction method and nodule volume was calculated by a semiautomatic software. The absolute percentage error (APE) of nodule volume relating to the reference acquisition and contrast-to-noise ratio was measured. Results: Nodule characteristic and tube voltage ( P < 0.0001) as well as the interaction between nodule characteristic and tube voltage ( P = 0.0026) contributed significantly to the mean difference of APE, while tube current did not ( P = 0.21). Post hoc analysis revealed no significant difference was found between the APE at 100 kV and 120 kV in both solid nodules (2.3 ± 0.4% vs 1.8 ± 0.6%, P = 0.14) and ground-glass opacities (6.0 ± 0.5% vs 4.9 ± 0.6%, P = 0.11). Exploratory analyses further showed that the APE at 100 kV with 10 mAs did not differ from that at 120 kV with 30 mAs in both solid nodules (2.5 ± 0.5% vs 1.7 ± 0.3%, P = 0.025, corrected P = 0.20) and ground-glass opacities (6.4 ± 0.4% vs 4.8 ± 1.0%, P = 0.0084, corrected P = 0.068). Conclusions: In our study, the exposure parameters with minimized radiation dose for accurate pulmonary nodule volumetry were found at 100 kV with 10 mAs, and the estimated effect radiation dose was as low as 0.2 mSv, suggesting the feasibility of further reducing radiation dose by decreasing tube voltage and current in LDCT lung screening. Abstract : Supplemental digital content is available in the text.